Evaluasi Kemampuan PDAM Kota Palangka Raya untuk Memenuhi Kebutuhan Kuantitas Air Bersih Tahun 2022 - 2032 - Ben Riva Haezer; Raden Haryo Saputra; Allan Restu Jaya (Jurnal Serambi Engineering, 2023)
The Regional Drinking Water Company (PDAM) is a regional business unit with the responsibility of distributing clean water to customers. For this reason, Palangka Raya PDAM needs to ensure that the quantity of clean water distributed can meet customer needs. This research is expected to be able to help Palangka Raya PDAM by projecting the number of customers until 2023 and determining the clean water needs that must be met within the projected timeframe. The projection of the number of customers is done using the geometric calculation method. From the results of the projected number of customers, the demand for clean water, both domestic and non-domestic, is calculated based on the Planning Criteria of the Directorate General of Cipta Karya PU (2000). Based on the results of the analysis, it was found that the projected number of customers in 2032 was 42,386 people, so the peak hour clean water demand for that year was 83.712 l/s with the current clean water distribution capability of Palangka Raya PDAM of 191.32 l/s, it can be said that until 2032 Palangka Raya PDAM is still able to meet the quantity needs of customers' clean water.Keywords: PDAM, clean water, customers, projection, distribution